A promise for spring : a novel - Sawyer, Kim Vogel (Minneapolis, Minn. : Bethany House, 2009)
After years of separation, English-born Emmaline Bradford is shocked by the conditions on Geoffrey's Kansas sheep ranch and wishes to return to England immediately. But Geoffrey offers a compromise: If Emmaline promises to stay until spring, he'll pay her return fare if she decides to go back to her home country.
Keywords: English -- United States -- Fiction; Immigrants -- United States -- Fiction; Ranchers -- Fiction; Kansas -- Fiction; United States -- History -- 1865-1898 -- Fiction; Love stories; Christian fiction; Historical fiction